2003
DOI: 10.1243/095440703321645115
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on soot formation and oxidation for a direct injection diesel engine

Abstract: A numerical cycle model is developed to investigate the soot production in a direct injection (DI ) diesel engine. The Surovikin and Fusco models for soot formation and the Nagle model for soot oxidation are used with the KIVA-3V code. In the Surovikin model, carbon radicals are produced from pyrolysis of fuel and soot particles grow through collisions with fuel molecules. In the Fusco model, the carbon radicals and acetylene are formed from pyrolysis of fuel. There, acetylene works for the growth of soot part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Acetylene is a well-known key PAH precursor, and its likely involvement in the formation of both pyrene and benzo­[ ghi ]­perylene suggests that it is a possible pyrolysis product of fossil diesel. For instance, Ciajolo et al found acetylene to be one of the major pyrolysis products in the combustion of tetradecane (a diesel-fuel surrogate), and several soot modeling studies include the pyrolytic production of acetylene as one of the steps in the soot formation process. Also apparent during this period is a decrease in the level of benzo­[b]­fluoranthene concurred with a greater increase in the level of indeno­[123- cd ]­pyrene (I­[123- cd ]­P) (see Figure S9b). Shukla and Koshi also suggested that phenylpyrene (phenyl addition to pyrene) is a precursor to the formation of indeno­[123- cd ]­pyrene; this is a possibility given the apparent availability of pyrene and the possibility of the presence of benzene among the pyrolytic products of fossil diesel as suggested by Xanthopoulou .…”
Section: Discussionmentioning
confidence: 99%
“…Acetylene is a well-known key PAH precursor, and its likely involvement in the formation of both pyrene and benzo­[ ghi ]­perylene suggests that it is a possible pyrolysis product of fossil diesel. For instance, Ciajolo et al found acetylene to be one of the major pyrolysis products in the combustion of tetradecane (a diesel-fuel surrogate), and several soot modeling studies include the pyrolytic production of acetylene as one of the steps in the soot formation process. Also apparent during this period is a decrease in the level of benzo­[b]­fluoranthene concurred with a greater increase in the level of indeno­[123- cd ]­pyrene (I­[123- cd ]­P) (see Figure S9b). Shukla and Koshi also suggested that phenylpyrene (phenyl addition to pyrene) is a precursor to the formation of indeno­[123- cd ]­pyrene; this is a possibility given the apparent availability of pyrene and the possibility of the presence of benzene among the pyrolytic products of fossil diesel as suggested by Xanthopoulou .…”
Section: Discussionmentioning
confidence: 99%
“…The model involved nine generic steps, i.e., fuel pyrolysis, precursor species (including acetylene) formation and oxidation, soot particle inception, particle coagulation, surface growth and oxidation. The numerical models have been continously developed since then with improved complexity and capability [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Soot formation is a persistent problem in fossil fuel combustion processes. The detailed kinetic mechanisms of soot formation in the pyrolysis, the combustion of hydrocarbons, and the soot particle dynamics have been studied extensively. Some numerical models have been developed to represent the physical and chemical processes of the soot formation in a diesel engine, which have improved the complexity and capability of soot models. A better understanding of the in-cylinder phenomena in a diesel engine is important for the development of NO X and particulate matter (PM) reduction strategies. The in-cylinder phenomena are complicated because they include the liquid fuel atomization, vaporization, ignition, and combustion processes accompanied with their emission formation.…”
Section: Introductionmentioning
confidence: 99%